Ultrasound in the diagnosis of cystic intra-abdominal lesions in children - a cross-sectional study from a tertiary care hospital in South India - Shikha, Sivasankara Pillai; Sreepriya, Pankajakshan Rema; Pillai Sandeep, Babu Bhaskaran; Mohanan, Kunnummal; Rajendran, Vadukkoot Raman; Nair Anish, Thekkumkara Surendran (Indian Journal of Child Health, 2018)
Introduction: Pediatric abdominal cystic swellings are very common in clinical practice, with widely variable differential diagnoses. Demarcation of the organ of origin and possible nature of pathology is hence very essential. Objective: The objective of the study was to study the pattern of ultrasound diagnosed intra-abdominal cystic swellings in children and to evaluate the role of ultrasound as the primary imaging modality in these lesions. Materials and Methods: A hospital-based cross-sectional study was conducted in the Department of Radiodiagnosis, of a Medical College of Kerala, India. Study participants were children below 12 years presenting with intra-abdominal cystic swellings who underwent abdominal ultrasonography. Direct visualization at the time of surgery or histopathological diagnosis was the gold standard. Percentage of concordance between radiological findings and final diagnosis was calculated. Significance of ultra-sonological findings associated to malignancy was assessed using Chi-square test. Results: In this study, the most common organ of origin for the cysts was the kidney, and the most common diagnosis was hydronephrosis. In 62 out of the total of 65 cases, ultrasound was able to rightly predict the pathology as to benign or malignant, with an overall accuracy of 95.3%. It had a sensitivity of 71.4%, specificity of 96.6%, and positive predictive value of 83.3%, and negative predictive value of 98.2% in determining the benign or malignant nature of a cyst. Conclusions: Ultrasound was found to be highly accurate in ascertaining the organ of origin, and in predicting whether a cyst is benign or malignant.